(untitled) (KULT_online, 2011)
Among the recent publications which seek to offer yet another re-definition of magical realism, Christopher Warnes’ study Magical Realism and the Postcolonial Novel: Between Faith and Irreverence accomplishes a double feat: while bringing into dialogue the development of both the term ’magical realism’ and the mode itself, Warnes develops two paradigms representing two major structural and functional tendencies in magical realism. One is based on an attitude of faith towards the cultural values represented by the supernatural in the texts, the other is characterized by an irreverent stance towards both the real and the supernatural. Applied to some of the key works of magical realism by Borges, Carpentier, Asturias, García Márquez, Rushdie, and Okri, the two paradigms produce acute readings of the cultural and political functions of the deployment of the mode in each individual work. The result is not a redefinition of magical realism, but a thought provoking re-contextualization which offers a typology capable of spanning the varieties of the mode.